Penaeus stylirostris densovirus proteins CP and NS1 interact with peritrophin of Litopenaeus vannamei. Issue 106 (November 2020) - Yang, Chunling; Liu, Qingyun; Peng, Min; Chen, Xiuli; Zhu, Weilin; Chen, Xiaohan; Li, Qiangyong; Zeng, Digang; Zhao, Yongzhen
Abstract: The Penaeus stylirostris densovirus (PstDNV) is a major virus of shrimps that severely harms the shrimp farming industry. Peritrophin is a peritrophic membrane protein with chitin binding activity. To examine the roles of peritrophin in viral infection, we used yeast two-hybrid to analyze the interaction between the Pacific white shrimp ( Litopenaeus vannamei ) peritrophin and PstDNV proteins (CP, NS1 and NS2). The yeast two-hybrid results showed that NS1 and peritrophin had an interaction, CP and peritrophin had an interaction as well, and NS2 had no interaction with peritrophin. We validated the interactions with GST pull-down assays. We then conducted RNA interference and qRT-PCR. The results showed that when pre-injection of dsRNA-peritrophin, the quantity of PstDNV in the shrimps injected with viruses was significantly lower than in the control group ( P  < 0.01), indicating the viral infection was decreased when the peritrophin gene expression was inhibited. The results indicated that peritrophin of L. vannamei participated in the PstDNV infection. Highlights: The PstDNV protein NS1 interacts with peritrophin of L. vannamei. The PstDNV protein CP also interacts with peritrophin of L. vannamei. When L. vannamei peritrophin gene expression was silenced, PsDNV proliferation in L. vannamei was reduced.